Adsorption and Decomposition of Formic Acid on Model Ceria and Pt/Ceria Catalysts - Lykhach, Yaroslava; Happel, Markus; Johanek, Viktor; Skala, Tomas; Kollhoff, Fabian; Tsud, Nataliya; Dvorak, Filip; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2013)
Adsorption and reaction of formic acid on stoichiometric CeO2(111), partially reduced CeO2-x, and Pt/CeO2(111) films prepared on Cu(111) were studied by means of synchrotron radiation photoelectron spectroscopy (SRPES), resonant photoemission spectroscopy (APES), infrared reflection absorption spectroscopy (IRAS), and temperature-programmed desorption (TPD). On all studied samples, the principal species formed during formic acid adsorption below 160 K were formate and molecular formic acid. In the presence of Pt particles, formate species were predominantly localized on Pt at 100 K, and on ceria at or above 300 K. Below 400 K, molecular formic acid decomposes to formate with partial release of CO2, CO, hydrogen, and water. Analysis of the TPD fragmentation suggests additional evolution of methane. Above 400 K, desorption of CO2, CO, hydrogen, and water is observed. This process is controlled by the stoichiometry of ceria and the presence of Pt particles. In particular, desorption of CO2 is suppressed on CeO2-x but is enhanced on Pt/CeO2. APES suggests that the reaction of formic acid does not alter the oxidation state of cerium cations on CeO2(111). By contrast, we observed significant reoxidation on partially reduced CeO2-x, between 250 and 400 K, followed by reduction between 400 and 500 K.

Adsorption, Ordering, and Metalation of Porphyrins on MgO Nanocube Surfaces: The Directional Role of Carboxylic Anchoring Groups - Schneider, Johannes; Kollhoff, Fabian; Schindler, Torben; Bichlmaier, Stephan; Bernardi, Johannes; Unruh, Tobias; Libuda, Jörg; Berger, Thomas; Diwald, Oliver (Journal of Physical Chemistry C, 2016)
The understanding of porphyrin adsorption on oxide nanoparticles including knowledge about coverages and adsorbate geometries is a prerequisite for the improvement and optimization of hybrid materials. The combination of molecular spectroscopies with small-angle X-ray scattering provides molecular insights into porphyrin adsorption on MgO nanocube dispersions in organic solvents. In particular, we address the influence of terminal carboxyl groups on the adsorption of free base porphyrins, on their chemical binding, on the metalation reaction as well as on the coverage and orientation of adsorbate molecules. We compare the free base form 5,10,15,20-tetraphenyl-21,23H-porphyrin (2HTPP) with the carboxyl-functionalized 5,10,15,20-tetrakis(4-carboxyphenyl)-21,23H-porphyrin (2HTCPP) and show that without carboxylic anchoring groups the free base form metalates on the nanocube surface and adopts a flat-lying adsorbate geometry. The saturation limit for flat-lying adsorption on nanocubes with an average edge length of 6 nm corresponds to 90 14 molecules per particle. This limit is surpassed when 2HTCPP molecules attach via their terminal carboxyl groups to the surface. The resulting upright adsorption geometry suppresses self-metalation, on the one hand, and allows for much higher porphyrin coverages, on the other (at porphyrin concentrations in the stock solution of 2 X 10(-2) mol.L-1). UV-vis diffuse reflectance results are perfectly consistent with conclusions from SAXS data analysis. The experiments reveal concentration dependent 2HTCPP coverages in the range between 0.4 to 1.9 molecules nm(-2) which correspond to the formation of a shell of upright standing porphyrin molecules around the MgO nanocubes. In contrast, after adsorption and metalation of nonfunctionalized 2HTPP the resulting porphyrin shells are in the range of a tenth of a nanometer and thus too thin to be captured by SAXS measurements. Related insights advance our opportunities to prepare well-defined nanohybrids containing highly organized porphyrin films.

Anchoring of carboxyl-functionalized porphyrins on MgO, TiO2, and Co3O4 nanoparticles - Kollhoff, Fabian; Schneider, Johannes; Li, Gao; Barkaoui, Sami; Shen, Wenjie; Berger, Thomas; Diwald, Oliver; Libuda, Jörg (Physical Chemistry Chemical Physics, 2018)
Hybrid materials consisting of functional organic molecules on metal oxide nanomaterials are key components in emerging technologies, for example in energy conversion and molecular electronics. In this work, we present the results of a comparative study of carboxyl-functionalized porphyrins on different oxide nanomaterials. Specifically, we investigated the interaction of 5(3-carboxyphenyl)-10,15,20-triphenyl-21,23H-porphyrin (2H-3-MCTPP) and 5(4-carboxyphenyl)-10,15,20-triphenyl-21,23H-porphyrin (2H-4-MCTPP), on MgO, TiO2, and Co3O4 nanoparticles (NPs) using isothermal and temperature-programmed diffuse reflection infrared Fourier transform spectroscopy (DRIFTS). We show that both porphyrins bind to the NPs, yielding stable monolayer films consisting of tilted surface carboxylates. In all cases, anchoring through the carboxylic acid group suppresses self-metalation of the porphyrin unit. Upon annealing, all anchored porphyrin films undergo metalation. The position of the acid group has no major influence on the reactivity. The same is true for the nature of the metal oxide, suggesting that the observed behaviour is general for most anchored porphyrin films on oxide nanomaterials.

Dynamic equilibria in supported ionic liquid phase (SILP) catalysis: in situ IR spectroscopy identifies [Ru(CO)xCly]n species in water gas shift catalysis - Bauer, Tanja; Stepic, Robert; Wolf, Patrick; Kollhoff, Fabian; Karawacka, Weronica; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Libuda, Jörg (Catalysis: Science and Technology, 2018)
Ru-based supported ionic liquid phase (SILP) systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). While previous studies suggest that Ru-carbonyl species play an important role in the mechanism, detailed knowledge on the catalytically active species is still missing. To identify these carbonyl complexes, we apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT). Investigations of an as-prepared [R(CO)3Cl2]2/ [C4C1C1Im]Cl/Al2O3 catalyst indicate splitting of the dimer induced by Cl−. Subsequently, an equilibrium between several [R(CO)xCly]n species is established, in which the IL serves as an effectively infinite Cl− reservoir. We find that the major species in the system freshly-prepared from [R(CO)3Cl2]2 is indeed [R(CO)3Cl3]−. A smaller amount of [R(CO)2Cl3]− and chloride-rich species [R(CO)2Cl4]2− or [RuCOCl4]2− are also found in the SILP. Similar Ru-carbonyl species are observed during carbonylation of RuCl3/ [C4C1C1Im]Cl/Al2O3, another potential WGSR catalyst. The response of [Ru(CO)3Cl2]2/[C4C1C1Im]Cl/Al2O3 to heating and/or CO dosing was probed in situ and the results confirm the presence of the equilibrium proposed above.
Keywords: SILP catalysis; in situ IR spectroscopy; [Ru(CO)xCly]n species

Porphyrin Metalation at the MgO Nanocube/Toluene Interface - Schneider, Johannes; Kollhoff, Fabian; Bernardi, Johannes; Kaftan, Andre; Libuda, Jörg; Berger, Thomas; Laurin, Mathias; Diwaid, Oliver (ACS Applied Materials and Interfaces, 2015)
Molecular insights into porphyrin adsorption on nanostructured metal oxide surfaces and associated ion exchange reactions are key to the development of functional hybrids for energy conversion, sensing, and light emission devices. Here we investigated the adsorption of tetraphenylporphyrin (2HTPP) from toluene solution on two types of MgO powder. We compare MgO nanocubes with an average size d < 10 nm and MgO cubes with 10 nm <= d <= 1000 nm. Using molecular spectroscopy techniques such as UV/vis transmission and diffuse reflectance (DR), photoluminescence (PL), and diffuse reflectance infrared Fourier-transform (DRIFT) spectroscopy in combination with structural characterization techniques (powder X-ray diffraction and transmission electron microscopy, TEM), we identified a new room temperature metalation reaction that converts 2HTPP into magnesium tetraphenyl-porphyrin (MgTPP). Mg2+ uptake from the MgO nanocube surfaces and the concomitant protonation of the oxide surface level off at a concentration that corresponds to roughly one monolayer equivalent adsorbed on the MgO nanocubes. Larger MgO cubes, in contrast, show suppressed exchange, and only traces of MgTPP can be detected by photoluminescence.
Keywords: porphyrin metalation; MgO cubes; solid-liquid interface; molecular spectroscopies; dye adsorption; hybrid materials

Sensitivity of CO oxidation toward metal oxidation state in ceria-supported catalysts: an operando DRIFTS-MS study - Kaftan, Andre; Kollhoff, Fabian; Thanh-Son Nguyen; Piccolo, Laurent; Laurina, Mathias; Libuda, Jörg (Catalysis: Science and Technology, 2016)
The oxidation of carbon monoxide has been studied on pristine CeO2, Rh-CeO2, and Pt-CeO2 powders prepared in one step by solution combustion synthesis (SCS). The reaction was cycled between an oxygenrich and a CO-rich feed with regard to the stoichiometric conditions. CO2 production was monitored by mass spectrometry, while the surface species were probed by operando DRIFTS (Diffuse Reflectance Infrared Fourier Transform Spectroscopy). Whereas the reaction starts above 150 degrees C on CeO2 and Rh-CeO2 and does not depend on the state of the surface (oxidized or reduced), the reaction on Pt-CeO2 shows strong dependency on the initial state and substantial activity is achieved at much lower temperatures with the CO-rich feed. We relate this result to the change in the oxidation state of Pt via strong interaction with ceria.

Thermally Activated Self-metalation of Carboxy-functionalized Porphyrin Films on MgO Nanocubes - Kollhoff, Fabian; Schneider, Johannes; Berger, Thomas; Diwald, Oliver; Libuda, Jörg (ChemPhysChem, 2018)
We investigated the adsorption of different free-base carboxyl-functionalized porphyrins, 5,10,15,20-tetrakis(4-carboxyphenyl)-21,23H-porphyrin (2H-TCPP) and 5(4-carboxyphenyl)-10,15,20-triphenyl-21,23H-porphyrin (2H-MCTPP), on MgO nanocubes combining IR, UV/Vis and photoluminescence emission spectroscopy. The thermal behavior of the films was monitored in-situ during annealing. Both porphyrins bind to the nanocubes via one and two acid groups respectively, yielding monolayer films consisting of tilted molecules. For 2H-TCPP, two acid groups remain free and give rise to a characteristic IR band. Self-assembly in a tilted adsorbate layer suppresses metalation at room temperature, in contrast to non-functionalized 2H-TPP, which adsorbs flat-lying. Upon heating, 2H-MCTPP undergoes full metalation at temperatures below 280 degrees C, whereas 2H-TCPP does not metalate at all. The hindered metalation reaction is attributed to the rigidity of the adsorbate film preventing complexation. Our results show that the properties of porphyrin films on oxides can be tuned in a wide range via the position and arrangement of carboxyl anchoring groups.
Keywords: porphyrin; oxide nanoparticles; infrared spectroscopy; UV; Vis spectroscopy; in-situ metalation